PENGARUH SEMANGAT KERJA PEGAWAI DAN KUALITAS PELAYANAN TERHADAP KEPUASAN MASYARAKAT PENGGUNA JASA PUSKESMAS WAY HALIM KOTA BANDAR LAMPUNG - ristra astriani (Universitas Bandar Lampung (UBL), 2016)
Public services are all forms of services, either in the form of public goods, and public services are organized by the central government and local governments to fulfill people's needs in order to implement the provisions of the legislation. In order to provide optimal public services, employees must have high morale. If an employee is able to provide a good service, the public service users will feel satisfied, and vice versa. Puskesmas Way Halim Bandar Lampung as one of the providers of public services in the health sector. However, the organization of health services by Puskesmas Way Halim still not optimal so that people's satisfaction for Puskesmas Way Halim Bandar Lampung has not been reached. The purpose of this study was to determine the effect of employee morale and quality of service to the satisfaction of public service users Puskesmas Way Halim Bandar Lampung. The method used was a survey and analysis of quantitative data. The results obtained; Simultaneously there is significant influence employee morale and quality of service to the satisfaction of public service users Puskesmas Way Halim Bandar Lampung by 42.1% and correlation between employee morale, quality of service and satisfaction of public service users Puskesmas Way Halim Bandar Lampung at 0.649 that included at a high level of correlation. The result of the calculation of multiple linear regression equation: Y = 9.742 + 0,303X1 + 0,360X2, and the calculation results obtained significant values (Sig) = 0,002 <α = 0.05. Based on this research, the implications suggested that, Head of Puskesmas Way Halim Bandar Lampung need to engage Puskesmas staff to participate in educational training for employee competence increased, it is necessary to evaluate the services provided by employees and conduct briefings then guidance to all employees to instill a mindset that employee as a public servant and Head of Puskesmas Way Halim Bandar Lampung need to give rewards and punishment for employees of Puskesmas Way Halim Bandar Lampung. Keywords: public service, employees morale, quality of service, satisfaction of public service users